ECG in the clinical and prognostic evaluation of patients with pulmonary arterial hypertension: an underestimated value. (March 2022) - Michalski, Tomasz Adam; Pszczola, Joanna; Lisowska, Anna; Knapp, Malgorzata; Sobkowicz, Bozena; Kaminski, Karol; Ptaszynska-Kopczynska, Katarzyna
Background: Pulmonary arterial hypertension (PAH) is a rare disease leading to right ventricular (RV) failure and manifests in decreasing exercise tolerance. Our study aimed to assess the usefulness of electrocardiographic parameters reflecting right heart hypertrophy as predictors of clinical status in PAH. Methods: The retrospective analysis included 26 patients, mean 49 ± 17 years of age, diagnosed with PAH, and eligible to undergo cardiopulmonary exercise test (CPET). The relations between ECG values and parameters obtained in procedures such as six-minute walk test (6-MWT), echocardiography, right heart catheterization (RHC), and CPET were analyzed. Results: P-wave amplitude in lead II correlated positively with CPET parameter of respiratory response: minute ventilation to carbon dioxide production slope (VE/VCO2 slope; r  = 0.436, p  = 0.029) and echocardiographic estimated RA pressure (RAP; r  = 0.504, p  = 0.02). RV Sokolow-Lyon index (RVSLI) positively correlated with echocardiographic parameters reflecting RV function, overload, and afterload–tricuspid regurgitation pressure gradient (TRPG; r  = 0.788, p  < 0.001), RV free wall thickness ( r  = 0.738, p  < 0.001), and mean pulmonary arterial pressure (mPAPECHO ; r  = 0.62, p  = 0.0016), respectively, as well as VE/VCO2 slope ( r  = 0.593, p  = 0.001) and mPAP assessed directly in RHC (mPAPRHC ; r  = 0.469, p  = 0.0497). R-wave in lead aVR correlated positively with TRPG ( r  = 0.719, p  < 0.001), mPAPECHO ( r  = 0.446, p  = 0.033), and several hemodynamic criteria of PAH diagnosis: positively with mPAPRHC ( r  = 0.505, p  = 0.033) and pulmonary vascular resistance ( r  = 0.554, p  = 0.026) and negatively with pulmonary capillary wedge pressure ( r  = −0.646, p  = 0.004). QRS duration correlated positively with estimated RAP ( r  = 0.589, p  = 0.004), vena cava inferior diameter ( r  = 0.506, p  = 0.016), and RA area ( r  = 0.679, p  = 0.002) and negatively with parameters of exercise capacity: peak VO2 ( r  = −0.486, p  = 0.012), CPET maximum load ( r  = − 0.439, p  = 0.025), and 6-MWT distance ( r  = −0.430, p  = 0.046). ROC curves to detect intermediate/high 1-year mortality risk (based on ESC criteria) indicate RVSLI (cut-off point: 1.57 mV, AUC: 0.771) and QRS duration (cut-off points: 0.09 s, AUC: 703 and 0.1 s, AUC: 0.759) as relevant predictors. Conclusion: Electrocardiography appears to be an important and underappreciated tool in PAH assessment. ECG corresponds with clinical parameters reflecting PAH severity.